Indigenous Ex Situ Conservation of Q'eqchi' Maya Medicinal Plant Resources at the Itzamma Garden-Indian Creek, Belize, Central America - Audet, Patrick (2012)
The Itzamma Garden and Medicinal Plant Project is a collaborative effort focused on identifying traditionally important plants used by the Q'eqchi' Maya of southern Belize. The Garden represents a cornerstone of the project where these plant resources (~130 in total, of which 102 have been identified to the species level) are cultivated ex situ as a means of providing primary healthcare by traditional healers. Here, we present a comprehensive agro-ecological survey of the Garden describing the layout and cultivation scenarios, development challenges encountered, and associated implementation strategies for improving site practices. A general recommendation for the adaptation of this strategy to other localities is the thorough depiction of ecological features based on interactions with local practitioners, for example, leading to the effective cultivation of plants, the enhancement of soil, and the surveillance of crop nutritional status and medicinal potency. We consider that the 'ethnobotanical garden approach' could provide a collaborative 'working model' for rural development, especially indigenous communities interfacing with their local agro-ecosystems.